2012
DOI: 10.22610/imbr.v4i1.963
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Ownership Structure at Different Level of the Financial Collapse in Listed Firms of Tehran Stock Exchange

Abstract: The main objective of this study is to compare ownership structure of different levels of collapse in listed companies of Tehran Stock Exchange (TSE). Study variables are the ownership structure that includes governmental ownership, private ownership (corporate ownership and individual ownership) and the different levels of collapse including latency stage, the stage of cash deficits and commercial and financial insolvency and complete collapse. Altman model (Z´- Score) is used to predict the collapse of firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…al., 2016). Capital that is financed by debt is called leverage, when at any increase in debt the leverage increases and thus the financial risk increases (Kangarlouei et. al., 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…al., 2016). Capital that is financed by debt is called leverage, when at any increase in debt the leverage increases and thus the financial risk increases (Kangarlouei et. al., 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, investors do not know about the specific risks because managers only know specific information about a firm's daily operations. Salem et al (2020), Karajeh (2019), Consoni et al (2017), Omar et al (2014), Kangarlouei et al (2013), Young (2012), dan Francis et al (2008) found that voluntary disclosure increases earnings quality. Thus, disclosure such as risk and voluntary disclosure has a close relationship with earnings quality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have carried out a study on earnings quality both in the international scope and within the scope of Indonesia. At global coverage, determinant factors on earnings quality such as fair value (Takacs et al, 2020;Pompili & Tutino, 2019;Rhee et al, 2018;Tutino & Pompili, 2018;Mauro et al, 2017;Šodan, 2015), corporate social responsibility (Rezaee et al, 2020;Mohmed et al, 2019;Bozzolan et al, 2015;Kim et al, 2012;Salewski & Zülch, 2012), voluntary disclosure (Salem et al, 2020;Karajeh, 2019;Consoni et al, 2017;Kangarlouei et al, 2013;Francis et al, 2008), diversification (Masud et al, 2017;El Mehdi & Seboui, 2011;Rodríguez-Pérez & van Hemmen, 2010), size (Phuong et al, 2020), financial stability (Riahi, 2020), audit quality (Alzoubi, 2018), profitability (Phuong et al, 2020), dividend (Mulchandani et al, 2020), dan capital structure (Phuong et al, 2020). Studies in Indonesia had investigated several determinant factors such as corporate governance (Sudirgo et al, 2021;Yasa et al, 2020;Saksessia & Firmansyah, 2020;Wijaya et al, 2020;Yasa et al, 2019;Nariman & Ekadjaja, 2018), size (Anam & Afrohah, 2020;Purnamasari & Fachrurrozie, 2020;Anggrainy & Priyadi, 2019;…”
Section: Introductionmentioning
confidence: 99%